The Child's elephant - Campbell-Johnston, Rachel (London ; Corgi Books, 2014)
Michael Morpurgo When a baby elephant is abandoned on the African savannah, a young boy named Bat takes her back to his village and cares for her. But Bat's grandmother explains that Meya cannot stay with them for ever - the call of the wild will always be sounding in her soul. Then frightening rumours arrive at the village; rumours of kidnapping, suffering and war. Bat and his friend Muka are snatched, and catapulted into a new life of unimaginable terror. Will the bond between Bat and Meya strong enough to save them?
Keywords: Africa -- Fiction; Child soldiers -- Africa -- Juvenile Fiction